2014
DOI: 10.4046/trd.2014.77.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy Caused by Pulmonary Tuberculosis: A Case Report

Abstract: Takotsubo cardiomyopathy (TTC) is defined as a reversible, acute ventricular dysfunction without any evidence of coronary artery obstruction. There have been reports of TTC caused by emotional or physical stress, drug use, hormone imbalance, or medical conditions such as pulmonary disease, sepsis, and trauma, but a relationship between TTC and pulmonary tuberculosis has not previously been reported. From our knowledge, this is the first report of TTC caused by pulmonary tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…With an increase in literature on TTC, a vast number of infectious agents are reported to precipitate the same . Table 1 summarizes the various bacterial, viral, and parasitic organisms reported to precipitate TTC in literature [6,[9][10][11][12]. Multiple studies have reported the precipitation of TTC following sepsis and septic shock as well [6,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an increase in literature on TTC, a vast number of infectious agents are reported to precipitate the same . Table 1 summarizes the various bacterial, viral, and parasitic organisms reported to precipitate TTC in literature [6,[9][10][11][12]. Multiple studies have reported the precipitation of TTC following sepsis and septic shock as well [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilus influenzae [20] L. pneumophila [22] Salmonella [22] Escherichia coli [6] Pseudomonas aeruginosa [6] Klebsiella pneumoniae [6] Klebsiella oxytoca [6] Francisella tularensis [23] Aeromonas hydrophila [6] Rickettsia Orientia tsutsugamushi [29] Miscellaneous bacteria Nocardia cyriacigeorgica [24] Acid fast stain Mycobacterium tuberculosis [10] Nontuberculous Mycobacterium [19] Viral Retrovirus HIV (human immunodeficiency virus) [11] DNA virus Cytomegalovirus [6] Hepatitis C [25] Parvovirus B19 [26] Herpes virus [6] Varicella zoster [7] RNA virus Influenza A * Influenza B [9] Dengue virus [8] Enterovirus [27] Hepatitis A [17] Norovirus [16] SARS-CoV-2 (COVID-19) [12] Fungal Candida glabrata [6] Cryptococcus neoformans [28] Parasites Protozoa Babesia [6] Helminth Paragonimiasis westermani [12] Taenia solium [6]…”
Section: Gram Positive Coccimentioning
confidence: 99%
“…Prior studied have linked several infections to TTC, including pulmonary infection and upper respiratory tract infection [9] , [10] . De Giorgi et al reviewed 27 reported case related to acute infection-induced TTC, found that it most frequently affects female and caused by bacterial infections.…”
Section: Discussionmentioning
confidence: 99%